Lymphodepleting chemotherapy with donor lymphocyte infusion post-allogeneic HCT for hematological malignancies is associated with severe, but therapy-responsive aGVHD - He, Fiona (Bone Marrow Transplant, 2016)
Donor lymphocyte infusion (DLI) is an option for relapsed hematologic malignancies or incomplete chimerism of non-malignant diseases following allogeneic hematopoietic cell transplantation (HCT). We analyzed the incidence of acute graft versus host disease (aGVHD) in patients treated with DLI. From 1995-2013, 171 DLIs were given to 120 patients. The cumulative incidence of post-DLI grade II-IV aGVHD was 31.6% (CI 25-42%, n=40; 12 grade II); grade III-IV 23.3% (CI 16-32%, n=28). GVHD after DLI (n=46) involved the skin in 70% (n=32), lower gastrointestinal (GI) 65% (n=30), upper GI 43% (n=20), and liver 35% (n=16). Patients receiving chemotherapy accompanying the DLI (chemo-DLI)(n=37) had more frequent aGVHD and particularly lower GI GVHD. Risk factors for grade II-IV aGVHD included: age > 40, chemo-DLI, malignant disease, and time from HCT to DLI < 200 days. aGVHD response to treatment at 8 weeks was complete in 40% and complete/partial (CR/PR) in 52%. We observed frequent, yet therapy-responsive aGVHD following DLI. Gastrointestinal GVHD in particular is a significant risk when giving chemotherapy prior to DLI. Improvements in DLI efficacy and GVHD management are still needed.